EXPERIENCE IN USING IMMUNOHISTOCHEMICAL METHOD IN DIFFERENTIAL DIAGNOSIS OF CENTRAL NERVOUS SYSTEM TUMORS - А. P. Nadeev; V. А. Zhukova; М. А. Kozyaev; М. А. Travin; К. Е. Yatsenko (Сибирский онкологический журнал)
The purpose of the study was to evaluate the nosological structure of central nervous system (CNS) tumors and the role of immunohistochemical assay in verification of their histogenesis.Material and methods. 162 biopsy and surgical specimens of CNS tumors obtained from neurosurgical departments of hospitals in Novosibirsk and Siberian Federal District in the period 2004–2013 were studied.Results. In the structure of primary CNS tumors, astrocytic tumors were the most common (47.9 %) followed by meningeal tumors (9.3 %), and oligodendroglial tumors (6.3 %) located predominantly in in the cerebral hemispheres of the brain (81 %). CNS metastases occurred on 11% of cases, there were mainly malignant epithelial tumor metastases. Inflammatory pseudotumors were observed in 3.1 % of cases. The use of immunohistochemistry with a broad panel of antibodies, mainly: pan-cytokeratin, vimentin, leukocyte common antigen, epithelial membrane antigen, glial fibrillary acidic protein allowed the histogenesis of CNS tumors to be clarified in 29.6 % of cases.